Sustainable intensification of agriculture as a tool to promote food security: A bibliometric analysis - Ajibade, Sinazo; Simon, Barbara; Gulyas, Miklos; Balint, Csaba (Frontiers in Sustainable Food Systems, 2023)
Agricultural producers around the world are pressurized to increase crop yields while protecting scarce natural resources and feeding the growing population. Sustainable intensification (SI) of agriculture is required to satisfy the growing populations’ nutritional needs, and therefore food security while limiting negative environmental impacts. Using bibliometric analysis, the present study investigates the global scientific output of sustainable intensification research from 2010 to August 2021. The data collected from the Web of Science (WoS) Core Collection was analyzed by bibliometric method and VOS viewer to determine the most productive countries, and organizations by collaboration analysis, including the keywords to analyze the research hotspots and trends, and the most cited publications in the field. From the 1610 studies published in Sustainable Agriculture by 6346 authors belonging to 1981 organizations and 115 countries, the study found an increased number of publications and citations in 2020, with 293 publications and 10275 citations. The United States ranked highest in countries collaborating with the most publications in the field. The availability of funding agencies from big economies explains the growing interest by developing countries in the SI of agriculture research due to the growing population, food insecurity, and access to limited land for farming. The occurrence of keywords like “food security”, “climate change”, “agriculture”, “ecosystem services”, “conservation agriculture”, “Sub-Sahara Africa”, “Africa”, “biodiversity”, and “maize” in both author and all keywords (author and index) reveals the significance of sustainable Intensification in Africa, as a solution to food insecurity under climate change conditions.